Influence of Sleep Deprivation in Series of Seizures Pattern in JME Patients - Zameer, Maniyar Roshan; M.A, Doshi; Jahan, Parveen; Umarji, B.N.; G, Shivannarayan.; G, Parthasaradhi; Muneer, Syed (International Journal of Innovative Research in Medical Science, 2017)
Background: Juvenile myoclonic epilepsy disease (JME) will disrupt the sleep and sleep deprivation can be trigger for seizures. JME is estimated around 3 in 10,000 with peak age at 14.5 to 15.5 years that affects both genders. All the JME patients identified at least one precipitating factors (PFs). The seizures usually occur after awakening and sleep deprivation (SD) was the most common precipitating factors PF (82%), stress is 64% and other factors involved 42% in younger JME patients. Seizures are precipitated by sudden awakening, sleep deprivation, emotional stress, photic stimulation, motor activity, and alcohol consumption. Juvenile Myoclonic Epilepsy (JME) is dependent on the sleep-wake cycle and SD is one of the most important factors for precipitating seizures. Objectives: The aim of this study was to investigate the effect of sleep deprivation in JME seizures related with psycho-sociological life. Methods: The case-control association study design was utilized to test the potential involvement of of sleep deprivation among Juvenile myoclonic epilepsy patients. In this study we evaluated the role of sleep deprivation to obtaining seizures pattern by personal interview in a series of 75 JME patients. The study has been followed up for four years in different Epilepsy centers, neuron centers and educational institutions in Andhra Pradesh and Telangana and Hyderabad-Karnatak region of Karnataka states. Result: The mean age of onset was 15.20 ± 7 years and at the time of presentation was 18 ± 7 years. Out of 75 JME patients 44 (58%) were males and 31 (41%) females. Sleep deprivation found in 26 (34.6%) JME patients, awakening presents 18 (24%), psychological stress had 12 (16%), menstruation 6 (8%), TV watching 4 (5.3%) and other factors triggering 9 (12%) in all JME cases as PFs. Interpretation & Conclusion: Indian patients with JME cases have difference in their clinic-electrical profile. Larger prospective studies are required to confirm these observations between them. Greater delay and avoidance of precipitation factors for treatment to the JME patients would greater the consequences of uncontrolled epilepsy.